2010
DOI: 10.4061/2010/780369
|View full text |Cite
|
Sign up to set email alerts
|

Influence of XRCC1 Genetic Polymorphisms on Ionizing Radiation‐Induced DNA Damage and Repair

Abstract: It is well known that ionizing radiation (IR) can damage DNA through a direct action, producing single- and double-strand breaks on DNA double helix, as well as an indirect effect by generating oxygen reactive species in the cells. Mammals have evolved several and distinct DNA repair pathways in order to maintain genomic stability and avoid tumour cell transformation. This review reports important data showing a huge interindividual variability on sensitivity to IR and in susceptibility to developing cancer; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 58 publications
(49 reference statements)
1
32
0
13
Order By: Relevance
“…The association of XRCC1 polymorphisms with glioma has been discussed in various studies Sterpone et al, 2010;Yosunkaya et al, 2010;Zipprich et al, 2010). A previous study conducted in the United State has shown polymorphisms of XRCC1 Gln399Arg is associated with increased risk of glioma in 373 glioma patients and 365 controls .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of XRCC1 polymorphisms with glioma has been discussed in various studies Sterpone et al, 2010;Yosunkaya et al, 2010;Zipprich et al, 2010). A previous study conducted in the United State has shown polymorphisms of XRCC1 Gln399Arg is associated with increased risk of glioma in 373 glioma patients and 365 controls .…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Turkey has indicated the XRCC1 399G allele carries a 3.5 times greater risk for glioma (Yosunkaya et al, 2010). The rs25487 located in the region of the BRCT1 binding domain, and mutations in the BRCT1 domain of BRCA1 have been implicated in the altered function of this tumor suppressor gene (Sterpone et al, 2010). Previous several studies have shown that XRCC1 399 variant allele was associated with increased gene expression of various cancers, such as head and neck cancer, ovarian cancer and hepatocellular carcinoma (Cheng et al, 2012;Kumar et al, 2012;Yuan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…DNA-repair genes act on a variety of pathways depending on the type of DNA-damage. The base excision repair (BER) pathway is involved mainly in the removal of oxidative DNA damage induced by reactive oxygen species [5]. The 8-oxoguanine DNA glycosyslase (OGG1) gene encodes a DNA repair protein that removes 8-oxo-7,8-dihydroguanine (8-oxoG) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many genes play a key role in BER like X-ray repair cross-complementing group 1 (XRCC1), OGG1 gene, PARP-1 and APE1 genes [55]. The XRCC1 interacts with several BER proteins such as DNA polymerase β, APE1, OGG1, PARP-1 and LIGIII [86]. X-ray Repair Cross Complementing 1 (XRCC1) is thought to function as a scaffolding protein in BER pathway [87].…”
Section: Therapeutic Intervention Of Drugs/ Inhibitors Against Ber Inmentioning
confidence: 99%